Unexpected Earnings, Abnormal Accruals, and Changes in CEO Bonuses - CHEN, Chih-Ying (Institutional Knowledge at Singapore Management University, 2007)
Prior research has found that the market premium for positive unexpected earnings is greater than the penalty for negative unexpected earnings and that the earnings response coefficients for positive (negatie) unexpected earnings are lower (higher) if abnormal accruals are income-increasing. In this study, we investigate whether the relation between changes in CEO bonuses and unexpected earnings (the pay-for-performance sensitivity) varies in a manner consistent with the differential market reactions described above. Based on a sample of US firms during 1993-2004, we find that the pay-for-performance sensitivity is higher when unexpected earnings are positive than when they are negative. For observations with small positive unexpected earnings, the pay-for-performance sensitivity is lower if the abnormal accruals are income-increasing. For observations with negative unexpected earnings, the pay-for-performance sensitivity is higher if the abnormal accruals are income-increasing. Further analysis shows that only the observations from the post-Enron period exhibit differential pay-for-performance sensitivities conditional on the sign of the abnormal accruals. Collectively, our results suggest that compensation committees increase the pay-for-performance sensitivity and discount the performance achieved by using income-increasing abnormal accruals in response to increased scruntity of executive compensation.